A Low-Profile Wearable Textile Antenna Using AMC for WBAN Applications at 5.8GHz - Bouamra, W.; Sfar, I.; Mersani, A.; Osman, L.; Ribero, J. M. (Engineering, Technology & Applied Science Research, 2022)
This paper presents a low-profile, wearable textile antenna, designed for Wireless Body Area Network (WBAN) applications operating in the 5.8GHz band for Industrial, Scientific, and Medical (ISM) applications. An Artificial Magnetic Conductor (AMC) structure was used to improve antenna performance and protect the human body from back-radiation. The antenna with the integrated AMC achieved a measured gain of 8.92dBi, an efficiency of 80%, a wide impedance bandwidth of 1.4GHz (24.1%), and SAR values of 0.00103 and 0.00034W/Kg for 10g and 1g tissues respectively. The proposed antenna was studied in a worn-on-body scenario using a multilayer numerical model of the human body. The influence of the thickness of each tissue layer of the human body was investigated. The results showed that the antenna maintained its performance, a stable gain was obtained, and the SAR values were also below the IEEE guidelines that guarantee the safety of the wearer.